The Impact of Typhoon Haiyan on Health Staff: A Qualitative Study in Two Hospitals in Eastern Visayas, The Philippines - Gil Cuesta, Julita; van Loenhout, Joris A. F.; de Lara-Banquesio, Maria L.; Isiderio, Juan M.; Aujoulat, Isabelle; Guha-Sapir, Debarati (Frontiers in Public Health, 2018)
Background and objective: Understanding how natural disasters affect their victims is key to improve prevention and mitigation. Typhoon Haiyan strongly hit the Philippines in 2013. In Leyte, health staff of two hospitals had a key role as responders, but also as victims. Scarce literature is available on how health staff may be affected when being disasters' victims. We therefore aimed to understand Haiyan's impact for health staff at personal and work level. Methods: We conducted semi-structured interviews in the two hospitals with doctors, nurses, midwives, watchmen and administrative staff in September 2016. We used a thematic analysis. Results: The three main aspects reported as influencing staff were accessibility, safety and emotional aspects. Accessibility was a main difficulty, which prevented some staff from reaching the hospital, causing other staff staying longer on-call. Personal and family safety were affected, and due to remaining on-call immediately after Haiyan, staff members reported lack of information about their family situation. Faith was an emotional aspect repeatedly mentioned as a coping mechanism, and commitment to serve patients was for some respondents an essential argument to stay on duty. Conclusions: Conflict between personal and professional concerns was present in health staff, making it difficult for them to prioritize work. Feeling unsafe was a common experience among health staff which influenced attendance to the hospital. Including temporary housing for staff and relatives close by the hospital can improve the extensive disaster risk during the typhoon season. In addition, established communication channels should be prioritized for staff on duty to find out about family members' wellbeing. We recommend faith and commitment to serve patients to be included in the preparedness programs in this setting.